2019
DOI: 10.1371/journal.pntd.0007985
|View full text |Cite
|
Sign up to set email alerts
|

Risk of dengue in Central Africa: Vector competence studies with Aedes aegypti and Aedes albopictus (Diptera: Culicidae) populations and dengue 2 virus

Abstract: IntroductionDengue is the most important mosquito-borne diseases worldwide but was considered scarce in West-Central Africa. During the last decade, dengue outbreaks have increasingly been reported in urban foci in this region suggesting major epidemiological changes. However, in Central Africa where both vectors, Aedes aegypti and Aedes albopictus are well established, the role of each species in dengue transmission remains poorly investigated. Methodology/Principal findingsField-collected strains of Ae. aegy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 48 publications
0
32
1
Order By: Relevance
“…aegypti and Ae. albopictus from Brazzaville, are able to ensure yellow fever virus [35], dengue virus [37], Zika virus [36] transmission. To clearly establish the epidemiological importance of each Aedes species in the Republic of the Congo, additional experiments including feeding behaviour patterns, covering additional locations, and spanning several seasons are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti and Ae. albopictus from Brazzaville, are able to ensure yellow fever virus [35], dengue virus [37], Zika virus [36] transmission. To clearly establish the epidemiological importance of each Aedes species in the Republic of the Congo, additional experiments including feeding behaviour patterns, covering additional locations, and spanning several seasons are needed.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti and Ae. albopictus collected in Brazzaville are able to transmit yellow fever virus [35], Zika virus [36], and dengue virus [37]. As there is no efficient vaccine (apart from yellow fever) and specific treatment against these diseases, vector control remains the cornerstone to prevent outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Mosquitoes were sampled as immature stages from August 2017 to April 2018 in several locations (Table 1) in Central Africa including Brazzaville in the Republic of Congo, and Yaoundé, Douala, Tibati, Maroua and Benoué National Park in Cameroon (Fig 1). Detailed characteristics of each collection site are presented in previous studies [22,23,32]. Larvae/pupae of Aedes mosquitoes collected from a minimum of 20 containers per site were transported to insectaries and pooled together according to the city and maintained until adults before morphological identification.…”
Section: Mosquito Collectionsmentioning
confidence: 99%
“…This species was suspected as the main vector during dengue and chikungunya outbreaks in Cameroon in 2006 [6]. It was also recently demonstrated that A. albopictus populations collected in different ecological settings in Cameroon are able to transmit dengue 2 virus [17].…”
Section: Introductionmentioning
confidence: 99%